The Scale of Approaching Accidentality of Events ? Its Design and Psychometric Properties - Sarzyńska-Mazurek, Ewa (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Changeability and accidentality are features of the modern world. Quite often it is difficult to predict the direction of changes. People approach differently unplanned and inexplicable things that happen in their life. The article presents the procedure of designing a Scale in order to investigate the attitude to accidental events and its psychometric properties. It was assumed that the attitude to accidental events may vary depending on the fact whether the examined person is to make a general statement or about a specific experience. Therefore, two versions of the scale were suggested. 286 people aged from 19 to 50 took part in the research. Both versions of the scale turned out to be tools of satisfactory reliability and accuracy. The factor analysis separated five factors in the first version of the scale and three factors in the second one.